New York City flavoured tobacco product sales ban evaluation. Issue 1 (12th February 2016) - Farley, Shannon M; Johns, Michael
Abstract : Introduction: The availability of flavoured tobacco products is associated with increased initiation and youth smoking. New York City prohibited all sales of flavoured cigars, cigarillos, little cigars, chew, snuff, snus, tobacco, pipe tobacco, roll-your-own tobacco, and dissolvables, excluding menthol, in October 2009; enforcement began in November 2010. This paper describes the sales ban evaluation. Methods: Data on retail tobacco sales of cigars, smokeless and other tobacco products such as pipe tobacco and roll-your-own, were analysed using interrupted time series methods, estimating changes in flavoured and non-flavoured tobacco product inflation-adjusted dollar sales overall, and by product type. Changes in ever use of flavoured tobacco products, any tobacco product use, and smoking prevalence among adolescents were estimated using multivariable logistic regression. Results: Sales of flavoured tobacco products declined overall (87%; p<0.001), and for flavoured cigars (86%; p<0.001) and flavoured pipe and roll-your-own (91%; p<0.001) following ban enforcement, while non-flavoured sales increased for cigars (5%; p=0.003) and pipe and roll-your-own (4%, p=0.030). In adjusted models, teens in 2013 had 37% lower odds of ever trying flavoured tobacco products (p<0.001), 28% lower odds of using any type of tobacco product (p=0.025), and a non-significant change in current smoking prevalence (p=0.114) compared with teens in 2010. Conclusions: Flavoured tobacco product sales and odds of ever using flavoured tobacco products or using any tobacco products among teens declined significantly after ban enforcement began. Collectively these findings demonstrate significant evidence that the flavoured tobacco products sales ban was successful in New York City, and could succeed elsewhere.